Evaluation of nutritive values of various non-conventional protein sources as potential feed ingredients for ruminants - SAMADI SAMADI; SITTI WAJIZAH; SAID MIRZA PRATAMA; ANURAGA JAYANEGARA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Samadi, Wajizah S, Pratama SM, Jayanegara A. 2023. Evaluation of nutritive values of various non-conventional protein sources as potential feed ingredients for ruminants. Biodiversitas 24: 4069-4078. The purpose of this study was to evaluate the nutritive values of various non-conventional protein sources as potential ingredients for ruminants, including chemical composition, in vitro digestibility, rumen fermentation, and methane emissions. Seven various non-conventional protein sources; grasshopper meal (GM), earthworm meal (EWM), fish by-product meal (FbPM), centipede meal (CM), snail meal (SM), ant eggs meal (AEM), mealworm meal (MWM) and one conventional protein source; soybean meal (SBM) were used in this study. All samples were dried at the temperature of 60oC for 24h and ground by the use of a hammer mill to pass a 1 mm sieve. The ground samples were utilized for further analysis, including chemical composition, in vitro digestibility, rumen fermentation, and methane emissions. Incubation was conducted with three replications in the water bath and temperature was maintained at 39ºC for 48h. All data were statistically analyzed using SPSS version 16 and the difference between treatments was stated (P<0.05). The results of the study indicated that all the samples contained various CP. The NDICP and ADICP in samples were low. All samples had high IVDMD and IVOMD, the highest in FbPM (P<0.01). Methane emission of the samples was lower than SBM (P<0.01).